Effectiveness of Vertebroplasty and Kyphoplasty for Pain Reduction in Patients with Sarcopenia and Osteoporosis - John H. Schilling; David Gimarc; Nicholas M. Pflederer; Jack Pattee; Michael Durst; MK Jesse; James Korf; Amanda Crawford; Corey K. Ho (Journal of Clinical Interventional Radiology ISVIR)
Purpose Vertebral compression fractures (VCFs) are common and associated with high morbidity including severe, debilitating pain. Percutaneous vertebroplasty/kyphoplasty is a demonstrated effective treatment for VCF. Sarcopenia has been implicated as a risk factor for VCF and refracture following cement augmentation, and as a risk factor for procedural complications in some populations; however, the effect of sarcopenia on VCF patients undergoing these procedures is unknown. This study aims to improve outcomes and patient selection by investigating the effects of highly common VCF comorbidities.